Kemampuan Memahami Kosakata Bahasa Indonesia Siswa Kelas III SD Kecamatan Banjar Barat - Faradina*, Faradina; Effendi, Rustam (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2022)
The ability of third-grade elementary school students in the West Banjarmasin sub-district in understanding the vocabulary of the Indonesian language field is exactly at the KKM and that is very worrying because if learning is not managed properly, the score could drop to a number below the KKM. The research was conducted to find out how the students’ understanding and ability among school clusters was in understand the vocabulary of the Indonesian language field. The research was conducted using qualitative and quantitative methods in the hope of producing more accurate and meaningful information. The results of the study showed the ability to understand the vocabulary of the Indonesian language field with an average value of 58.29 with details of the ability to understand the vocabulary of the Indonesian language field in urban elementary schools 61.24 and suburban areas 52.66. Based on the results of the comparative test, the ability of students in urban and suburban areas is significantly related and the inter-cluster relationship is also significant. ABSTRAK Kemampuan siswa kelas III Sekolah Dasar se-Kecamatan Banjarmasin Barat dalam memahami kosakata bidang ilmu bahasa Indonesia nilainya persis pada KKM dan itu sangat menghawatirkan karena jika pembelajaran kurang dikelola dengan baik, nilai itu bisa saja menurun ke angka di bawah KKM. Penelitian dilakukan untuk mencari tahu bagaimana pemahaman dan kemampuan siswa antargugus sekolah dalam memahami kosakata bidang ilmu bahasa Indonesia. Penelitian dilakukan dengan menggunakan metode kualitatif dan kuantitatif dengan harapan dapat menghasilkan informasi yang lebih akurat dan lebih bermakna. Hasil peneitian menunjukkan kemampuan memahami kosakata bidang ilmu bahasa Indonesia nilai rata-rata 58,29 dengan rincian kemampuan memahami kosakata bidang ilmu bahasa Indonesia SD Negeri daerah perkotaan 61,24 dan daerah pinggiran kota 52,66. Berdasarkan hasil uji komparasi terhadap kemampuan siswa daerah perkotaan dan daerah pinggiran berhubungan secara signifikan dan begitu juga hubungan antargugus juga signifikan. Kata Kunci: bahasa Indonesia; kosakata; pemahaman